Novel UV led photopolymerization and characterization for polyacrylamide and poly (n-isopropylacrylamide) hydrogels - Ayub, Nur Farizah (2016)
In this study, polyacrylamide (PAAm) and poly(N-isopropylacrylamide) (PNIPAAm) hydrogels were synthesized via ultraviolet light-emitting diode (UV LED) (? ~ 365 nm) photopolymerization system. UV LED technology has offered better alternative than UV mercury (Hg) system for curing technology especially for temperature-sensitive polymeric hydrogels as it can be operated without heat generation and with fast curing response. The control experiment using commercial photoinitiators has shown that UV LED system was suitable to polymerize hydrogels provided that; photoinitiator has the overlap emission with UV LED spectra. However, most commercial photoinitiators have limited solubility in water. Thus, suitable water soluble photoinitiator (WSPI) for UV LED system (i.e. ? ? 330-365 nm) was prepared in order to synthesize UV LED curable hydrogel in purely water formulation. The water soluble photoinitiator was obtained from complexation of 2,2-dimethoxy-2-phenylacetophenone (DMPA) and methylated-ß-cyclodextrin (MßCD). According to the results presented in this work, high monomer conversion (> 90 %) was achieved with WSPI-initiated hydrogels. The non-responsive and responsive behavior of PAAm and PNIPAAm hydrogels towards temperature were demonstrated by swelling and rheological measurements. In addition, swelling and rheological methods gave good correlation for determination of mesh sizes. From rheological measurements, the elastic modulus (G') was higher than the loss modulus (G?) and both parameters were independent to the measured frequency window. It has shown that UV LED cured hydrogels possessed ideal rubber characteristic. Tensile properties of the hydrogels showed similar trend curve as commercial contact lenses reported in the previous study. Clearly, this study has revealed that UV LED system is a good tool to synthesize hydrogels by using the excellent choice of photoiniator.